Evaluation of the implementation of the halal assurance system for mininori products at cv panda food, special region of yogyakarta - Anggi, Anggi; Rahayu, Wahidah Mahanani (Journal of Halal Science and Research, 2022)
Halal is one of the essential requirements for seasonal consumers in consuming food products. CV Panda Food is one of the snack manufacturers that requires a halal certification for products to be distributed. This observation aims to determine whether the raw materials used have received a halal certificate and to analyze the suitability of the Halal Assurance System (SJH) application based on the HAS 23000 standard. The methods used in data collection are observation, interviews, direct practice, documentation, and literature study. The evaluation was carried out by checklist analysis and adjusted to 11 HAS 23000 LPPOM MUI requirements. The results are that all raw materials have received Halal approval from the MUI. After conducting a suitability analysis of the CV Panda Food Halal Assurance System implementation, there are still deficiencies; the requirement that must be corrected first are written procedures for critical activities, training, halal management team, and halal policies.